Horror to the extreme : changing boundaries in Asian cinema - Choi, Jinhee; Wada-Marciano, Mitsuyo (TransAsia--screen cultures., 2009)
This title compares production and consumption of Asian horror cinemas in different national contexts and their multidirectional dialogues with Hollywood and neighbouring Asian cultures. The essays highlight common themes such as technology digital media, and transnational co-productions.